Mufrodat 4.0: Efektivitas Integrasi AI dan Problem Based Learning di Kelas Bahasa Arab MTs Surabaya - Salman Alfarisi; Ida Miftahul Jannah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The digital era presents both challenges and opportunities in Arabic vocabulary learning. The integration of Artificial Intelligence (AI) introduces a more individualized, interactive, and effective approach to vocabulary management while addressing the limitations of traditional methods. This study examines the effectiveness of integrating AI with the Problem-Based Learning (PBL) model through the innovation of Mufrodat 4.0 in Arabic language learning at an Islamic junior high school (MTs) in Surabaya. The research employed a quasi-experimental method with a pre-test and post-test design involving experimental and control groups, using vocabulary tests, observations, and motivation questionnaires as instruments. The findings indicate that Mufrodat 4.0 significantly improves students’ vocabulary mastery and learning motivation compared to conventional methods. The integration of AI and PBL in this model fosters a more interactive, contextual, and learner-centered learning process. It can be concluded that Mufrodat 4.0 is effective for Arabic language instruction at the Madrasah Tsanawiyah level and holds strong potential as a strategic innovation in responding to the challenges of digital-era education. Keywords: Mufrodat 4.0, Artificial Intelligence (AI), Problem-Based Learning (PBL), Arabic Language, Learning Effectiveness, Islamic Junior High School (MTs)